2020
DOI: 10.1007/s11277-020-07277-3
|View full text |Cite
|
Sign up to set email alerts
|

On Platform to Enable the Cognitive Radio Over 5G Networks

Abstract: With the increase in the number of communication devices, the requirement for higher bandwidth is essential. To achieve this goal, research and industrial communities have both suggested that future wireless systems will take advantage of the numerous emerging technologies. Utilization of Cognitive Radio (CR) for the next-generation Fifth Generation (5G) communication technology is the major advancement for getting a higher bandwidth in a cellular communication network. In this paper, we present a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 132 publications
(127 reference statements)
0
16
0
Order By: Relevance
“…Recently, the FCC has committed to the implementation of the shared utilization of the 3550-3650 MHz bands [102]. CR, based on a software-defined radio, offers the opportunity for flexible spectrum access in wireless systems [103]. It is also regarded as one of the key players of the current 5G cellular network.…”
Section: Cognitive Radiomentioning
confidence: 99%
“…Recently, the FCC has committed to the implementation of the shared utilization of the 3550-3650 MHz bands [102]. CR, based on a software-defined radio, offers the opportunity for flexible spectrum access in wireless systems [103]. It is also regarded as one of the key players of the current 5G cellular network.…”
Section: Cognitive Radiomentioning
confidence: 99%
“…Both single-sided and double-sided auctions are represented in the figure. In today's communication world which is moving towards 5G technology (Hu et al, 2018;Hindia et al, 2020), CR can play an important role. To achieve higher capacity in 5G network, CR can be incorporated to provide flexibility in spectrum availability.…”
Section: Auction For Spectrum Allocation In Crnmentioning
confidence: 99%
“…It is observed that FR1 is almost fully occupied and has limited resources to be utilized for the current 5G network, whereas FR2 is the frequency range where most of the spectrum untapped, and it can be easily exploited for future cellular communication [9]. To satisfy the user's requirements of cellular technology, various types of techniques were introduced, such as mm-wave [10,11], Relay Node (RN) [12], Massive Multiple Input Multiple Output (M-MIMO) [13], Heterogeneous Network (HetNet) [14], Carrier Aggregation (CA) [15], Cognitive Radio (CR) [16], Ad-hoc network [17], Beamforming [11], Four Single-Sideband [18], and so on. These methods are a joint venture of previous and novel wireless technologies [19].…”
Section: Introductionmentioning
confidence: 99%